ABDULLA QAHHOR THROUGH THE EYES OF WORLD WRITERS - Yoqubov Islomjon Ahmedjanovich (Galaxy International Interdisciplinary Research Journal, 2021)
Abdulla Kahhor (1907-1968) was analyzed and discussed in this article in light of independent Uzbekistan’s free and autonomous thought. The opinions of A. Kahhor articulated by twentieth-century literary scientists, poets, and translators who knew A. Kahhor, spoke with him, and collaborated creatively were re-perceived.